Archetypal Motifs and Cultural Symbolism in Magar Sorathi Folklore: A Jungian and Motif-Index Analysis - Pun, Gobinda Prasad (Mindscape: A Journal of English & Cultural Studies, 2025)
This paper explores the archetypal motifs found in the Sorathi tradition of Nepal’s Magar people, their cultural significance, psychological interest, and ritual function. Relying on Carl Gustav Jung’s archetype theory and collective unconscious, and Stith Thompson’s Motif-Index system, the paper identifies and interprets repeating motifs that control the Sorathi narrative and its performing arts traditions. The research is based on a comprehensive survey of the Sorathi ballad, its ritual performances like invocation, binding, and raising-of-the-spell ceremonies, along with accompanying ethnographic and literary sources. Findings indicate six significant clusters of motifs: ritual and performative motifs; natal and maternal motifs; social and ethical motifs; nature motifs; taboo and sexual motifs; and trickster and reversal motifs. Every cluster conveys symbolic significance in relation to fertility, social order, moral justice, and spiritual rebirth, and collectively they define the Magar worldview and validate communal identity. The article argues that Sorathi is not merely a traditional oral entertainment but a cultural repository keeping ancestral memory, storing moral virtue, and transmitting universal archetypal images in uniquely local forms. This research enlivens folklore research through the convergence of psychological, cultural, and ritual perspectives and underscores the importance of recording oral tradition in Nepal for comparative mythology and heritage preservation.